2013
DOI: 10.3389/fnsys.2013.00072
|View full text |Cite
|
Sign up to set email alerts
|

Representation of individual elements of a complex call sequence in primary auditory cortex

Abstract: Conspecific communication calls can be rhythmic or contain extended, discontinuous series of either constant or frequency modulated harmonic tones and noise bursts separated by brief periods of silence. In the guinea pig, rhythmic calls can produce isomorphic responses within the primary auditory cortex (AI) where single units respond to every call element. Other calls such as the chutter comprise a series of short irregular syllables that vary in their spectral content and are more like human speech. These ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This was in parallel with many electrophysiological studies that recorded responses to similar vocalizations at neuronal levels (Bauer et al, 2002;Mayko et al, 2012;Pincherli Castellanos et al, 2007;Suta et al, 2007;Wallace et al, 2005Wallace et al, , 2013. The UHF vocalizations used in this study was in the category of "50 kHz calls" (the parallel category "20 kHz calls" was not examined in this study) (Brudzynski, 2009;Portfors, 2007).…”
Section: Bold Responses To Social Vocalizationsmentioning
confidence: 67%
“…This was in parallel with many electrophysiological studies that recorded responses to similar vocalizations at neuronal levels (Bauer et al, 2002;Mayko et al, 2012;Pincherli Castellanos et al, 2007;Suta et al, 2007;Wallace et al, 2005Wallace et al, , 2013. The UHF vocalizations used in this study was in the category of "50 kHz calls" (the parallel category "20 kHz calls" was not examined in this study) (Brudzynski, 2009;Portfors, 2007).…”
Section: Bold Responses To Social Vocalizationsmentioning
confidence: 67%
“…Other studies, particularly in the guinea pig, have reported spiking responses in which the temporal structure of communication calls is well-preserved 9 , 46 , 47 . Such responses are called “isomorphic”, since the spiking and the stimulus have similar shape over time.…”
Section: Discussionmentioning
confidence: 94%
“…birds, bats, and non-human primates) emit communication calls with multiscale temporal structures. These calls, often referred to as sequences, are typically composed of individual acoustic elements like syllables, or groups of syllables, which ultimately make up whole vocalizations 4 , 9 11 . For example, in bats, syllabic structures have been observed in the context of distress calling 2 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These investigations in model systems led to the discovery of cricket-song selective neurons and their contribution to the females' phonotaxis behavior [77], of call selective neurons in frogs [78] and guinea pigs [79], of song selective neurons in songbirds [7,[80][81][82], of neurons selective to the echolocation signal in bats [5], and of brain regions selective for conspecific calls in primates [83]. Selectivity for conspecific communication calls can be reflected not only in the mean rate of single neurons but also (and sometimes only) in time-varying responses [84,85] or ensemble responses [86,87]. Thus, the auditory system is not only selective to natural sounds in a broad sense but appears to also exhibit specialized circuitry for the sole purpose of detecting and processing conspecific communication calls.…”
Section: Animal Vocalizationsmentioning
confidence: 99%